NopD of Bradyrhizobium sp. XS1150 Possesses SUMO Protease Activity - Xiang, Qi-Wang; Bai, Juan; Cai, Jie; Huang, Qin-Ying; Wang, Yan; Liang, Ying; Zhong, Zhi; Wagner, Christian; Xie, Zhi-Ping; Staehelin, Christian (Frontiers in Microbiology, 2020)
Effectors secreted by the type III protein secretion system (T3SS) of rhizobia are host-specific determinants of the nodule symbiosis. Here, we have characterized NopD, a type III effector of Bradyrhizobium sp. XS1150. NopD was found to possess a functional N-terminal secretion signal sequence that could replace that of the NopL effector secreted by Sinorhizobium sp. NGR234. Recombinant NopD and the C-terminal domain of NopD alone can process small ubiquitin-related modifier (SUMO) proteins and cleave SUMO-conjugated proteins. Activity was abolished in a NopD variant with a cysteine-to-alanine substitution in the catalytic core (NopD-C972A). NopD recognizes specific plant SUMO proteins (AtSUMO1 and AtSUMO2 of Arabidopsis thaliana; GmSUMO of Glycine max; PvSUMO of Phaseolus vulgaris). Subcellular localization analysis with A. thaliana protoplasts showed that NopD is a nuclear effector that accumulates in nuclear bodies. NopD, but not NopD-C972A, induces cell death when expressed in Nicotiana tabacum. Likewise, inoculation tests with constructed mutant strains of XS1150 indicated that nodulation of Tephrosia vogelii is negatively affected by the protease activity of NopD. In conclusion, our findings show that NopD is a symbiosis-related protein that can process specific SUMO proteins and desumoylate SUMO-conjugated proteins.